PENGARUH PENERAPAN SISTEM E-FILING, E-FORM, E-SPT, E-BILLING TERHADAP KEPATUHAN WAJIB PAJAK UMKM (STUDI KASUS UMKM COFFEE SHOP DI KABUPATEN PATI) - Taufiq Andre Setiyono; Talitha Mazmur Kinanthining Christi (Jurnal Edueco, 2022)
This study aims to empirically examine the effect of the application of the e-filing sistem, e-form, e-spt and e-billing on the compliance of coffee shop SME taxpayers in Pati. The data used are primary data obtained from 30 Coffee Shop respondents. The analytical method used is IBM SPSS26 Multiple Linear Regression Analysis to determine the effect of independent variabels on variabels. The results of this study indicate that e-filing has a negative and significant effect on taxpayer compliance, e-form has a positive and significant effect on taxpayer compliance, e-SPT has a negative and significant effect on taxpayer compliance, e-billing has a negative and significant effect on compliance. taxpayer